Hyperpigmentation following Treatment of Frontal Fibrosing Alopecia - Pérez Rodríguez, Irma Margarita; García Melendez, Martha Elena; Eichelmann, Kristian; Vázquez Martínez, Osvaldo Tomás; Ocampo Candiani, Jorge (2013)
Introduction: Frontal fibrosing alopecia (FFA) is a scarring alopecia characterized by progressive recession of the frontotemporal hairline. Current treatment is aimed at stopping progression, and the combination of dutasteride and pimecrolimus is the most effective therapy. Side effects associated with dutasteride are erectile dysfunction as well as breast tenderness and enlargement, while pimecrolimus produces a burning sensation. Case Report: We present a 57-year-old postmenopausal female with a 3-year history of a scarring alopecic plaque in her frontotemporal region. Biopsy confirmed the diagnosis of FFA, and she was started on dutasteride 0.5 mg p.o. q.d., and later, topical pimecrolimus 1% b.i.d. was added. Eight months after initiating treatment, she showed hyperpigmentation on her metacarpophalangeal and interphalangeal joints, as well as on the cheeks and on the chin; dutasteride and pimecrolimus were discontinued. After 5 months of follow-up, her hyperpigmentation improved by 80% only by using photoprotection. Conclusion: Because of the variable clinical course of FFA, treatment is focused on halting its progression. Several therapeutic agents have been evaluated and the combination of dutasteride and pimecrolimus has shown a high response rate. There is no reported evidence of hyperpigmentation associated with this combination.